2017
DOI: 10.1002/mrm.26820
|View full text |Cite
|
Sign up to set email alerts
|

Predicting IDH mutation status in grade II gliomas using amide proton transfer‐weighted (APTw) MRI

Abstract: Purpose To assess the APTw-MRI features of isocitrate dehydrogenase (IDH)-wildtype and IDH-mutant grade-II gliomas and to test the hypothesis that the APTw signal is a surrogate imaging marker for identifying IDH mutation status preoperatively. Methods 27 patients with pathologically confirmed low-grade glioma, who were previously scanned at 3T, were retrospectively analyzed. The Mann-Whitney test was used to evaluate relationships between APTw intensities for IDH-mutant and IDH-wildtype groups, and the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 76 publications
(118 reference statements)
7
110
0
Order By: Relevance
“…However, our study suggests that rNOE and APT effects are not equally associated with treatment response in glioma. Hence, there may be other mechanisms/factors influencing the contrast, eg, histopathological characteristics such as tumor grade and molecular features including protein conformation, pH, or genetic subtypes such as IDH mutation status . The analysis of larger study cohorts with detailed histological and molecular data would allow further investigation of this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study suggests that rNOE and APT effects are not equally associated with treatment response in glioma. Hence, there may be other mechanisms/factors influencing the contrast, eg, histopathological characteristics such as tumor grade and molecular features including protein conformation, pH, or genetic subtypes such as IDH mutation status . The analysis of larger study cohorts with detailed histological and molecular data would allow further investigation of this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…APTw MRI, based on the concentration levels of endogenous cellular proteins and peptides in tissue, has become increasingly recognized as a promising technology in detecting tumors because of its advantage of nonionizing‐radiation and its contrast‐free nature . Several previous studies have reported that APTw imaging was useful in differentiating malignant tumors from benign or normal tissues . The mean APT of malignant tumors in head and neck was significantly higher than that of brain tissue, muscle tissue, and benign tumors .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, coagulation necrosis largely restricts the mobility of proteins, leading to hypointensity on APTw images, which is similar to proteins in cooked egg white, showing almost zero APT effect . Furthermore, the intratumoral vessels in low‐grade gliomas always demonstrate hyperintensity on APTw images, which highly resembles the hyperintensity from the malignant tumors. The scenario is similar to liver, where the intrahepatic portal system and hepatic arteries always show hyperintensity on APTw images.…”
Section: Challenging Issues and Controversiesmentioning
confidence: 98%
“…However, the MRS detection of 2‐HG in IDH‐mutant gliomas requires a large tumor volume, and is time‐consuming, which limits its clinical application. In two recent retrospective studies, Jiang et al have shown that the APTw signal has potential as an imaging biomarker for identifying IDH mutation status in low‐grade gliomas and MGMT methylation status in high‐grade gliomas . These preliminary APTw MRI results showed that IDH‐wildtype lesions were typically associated with relatively high APTw intensities, compared with IDH‐mutant lesions.…”
Section: Current Applicationsmentioning
confidence: 99%